Psychiatric problems in the primary health care context: a study in the Border-Kei area - Cook, Jacqueline (Rhodes University, Faculty of Humanities, Department of Psychology, 1996)
A clinic survey was undertaken to investigate the nature of psychiatric problems experienced by the primary health care (PHC) patient population in the Bisho-King William's Town area of the Eastern Cape Region. The study took as its point of departure research findings which attest to the high rate of psychiatric distress amongst this population group in different parts of the world and ohservations regarding the form of presentation in terms of physical complaints. Hypotheses posited relationships between psychiatric problems experienced by patients attending PHC clinics in the study area and four types of variables, namely; somatic complaints, socio-demographic characteristics, patterns of health service utilisation and patient satisfaction with health services. Using a quasi-experimental descriptive approach, a two-stage screening procedure sorted the patient sample into three groups on the basis of the degree of psychiatric symptomatology experienced. The triangulation of the results of between-groups analyses with case materials recorded during psychiatric interviewing provided for an ethnographic account of the cultural experience of distress in the study area. The screening process used standard instruments, the Self-Reporting Questionnaire (SRQ) in the first stage and the Present State Examination (PSE) in the second stage. A pilot study was conducted prior to the fieldwork for the main study. Using the SRQ, thirteen psychiatric paticnts and 31 general PHC patients were sampled for the pilot study and 148 PHC patients were sampled for the main study. Using the PSE, 11 and 57 PSE interviews were conducted in the pilot and main studies respectively. Between-groups analyses used chi-square and F-statistics to investigate possible associations with identified patient correlates (P<0.5). These were socio-demographic, utilisation and satisfaction variables, measured by a separate face-valid self-response instrument compiled for the purposes of this study. Psychiatric symptomatology was found to be statistically significantly related to age, marital status and educational level. Further, patients experiencing more psychiatric symptomatology reported significantly more illnesses requiring treatment, longer consultation periods and a greater number of sick bed days. No statistically significant relationships were found between psychiatric symptomatology and number of children, number of failures at school, amount of treatment utilised, number of consultations, or patient satisfaction with services. Descriptive analyses of symptom and syndrome profiles found certain somatic complaints to be particularly prevalent amongst the patient sample. These include headaches and various tension pains, decreased energy levels and digestive problems. Qualitative analysis of interview data found that many somatic and psychiatric problems experienced constitute culturally defined and meaningful experiences, especially 'umbilini' (or nerves), 'ufufunyana' (a possession state), and accusations of witchcraft. Interpretation of complaints from the local traditional healing perspective, revealed a more complex mode of communication between patients and the health delivery system than may be accounted for in terms of a simple biomedical model. The interpretive analysis in the study showed that some forms of presentation incorporating somatic symptoms, such as 'nerves' may he viewed as help seeking behaviour of the socially unempowered. Implications of the results are discussed in relation to the need for improved identification and management of psychiatric distress at PHC level facilitated by a better developed referral network and closer interaction between biomedical and anthropological perspectives.
Keywords: Primary health care -- South Africa; Mental health services -- South Africa; Black people -- Mental health -- South Africa